As relações de saber-poder na construção da Base Nacional Comum Curricular (BNCC) no Brasil - MENDES, Elkson Almeida (2022)
This text presents some analyzes part of the PIBIC 2019-2020 Research Project “The effectiveness of the National Curricular Common Base (BNCC) in the Education Network of the Municipality of Abaetetuba: biopolitical strategy of government of the school population” which aims to analyze the production of biopolitics in the curriculum constituted based on the BNCC, questioning the historical conditions of BNCC emergence and the biopolitical devices in the curriculum built by the Municipal Education Department of Abaetetuba based on the BNCC. The clipping presented here discursively analyzes some documents that guide the logic of uniformization and homogenization of the curriculum from the perspective of a Common National Curricular Base, such as the LDB 99/96, the National Education Plan. The theoretical-methodological framework is guided by authors such as Aguiar and Dourado (2018), Lopes (2018), Foucault (2008a), Gadelha (2009), Gadelha; Pulino (2012), Oliveira; Kohan (2012), Ambrózio (2012), Veiga-Neto, Lopes (2007). The analysis of the discursive production that constitutes the documents highlights the historical conditions of the emergence of a "Base" that is defined as national, common and curricular, but without making any epistemological discussion of the knowledge-power relations that establish such notions, of the "policy truth” that constitutes it in the current neoliberal Brazilian society, producing “truth effects” in the curricular proposals of states and municipalities.